Impact of Millennium Development Goals on Universal Basic Education in Bokkos Local Government: Motivation for Teachers Confidence Behavior - Macqual, Stephen Maren; Salleh, K. MohD; Hutkemri, H. (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
The objective of this research work was to examine the impact of millennium development goals on the achievement of universal primary education in Bokkos local government area of plateau state. A cross sectional survey otherwise known as sample survey was used as the design for the study. A sample of 400 hundred students was drawn from the population of the study through simple random sampling technique. An instrument called Contribution of Millennium Development Goals to Universal Basic Education Questionnaire (CMDGQ) was used to collect data from the 400 sampled students out of the population. Descriptive statistics was used to analyzed the research questions while the hypotheses were tested at 0.05 level of significance using t-test statistical technique.  The statistical package for social sciences (SPSS) was used to run the descriptive statistics and test the research hypotheses. The findings of from the study reveal that the participation of millennium development goals to universal basic education is not adequate and there was no significance difference between the impact of millennium development goals and universal basic education boards to universal basic education schools in infrastructural facilities. The study recommended that millennium development goals as well as universal basic education boards should increase their involvement in universal basic education for better attainment of economic development. Keywords: Millennium Development Goals, Universal Basic Education, Confidence Behavior.